Consideration of demand rate in overall equipment effetiveness (OEE) on equipment with constant process time - Perumal Puvanasvaran; Y. S. Teoh; C. C. Tay (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The paper is primarily done on the purpose of introducing new concept in defining the Overall Equipment Effectiveness (OEE) with the consideration of both machine utilization and customer demand requested. Previous literature concerning the limitation and difficulty of OEE implementation has been investigated in order to track out the potential opportunities to be improved, since the OEE has been widely accepted by most of the industries regardless their manufacturing environment. Design/methodology/approach: The paper is conducting the study based on literature review and the computerized data collection. In details, the novel definition and method of processing the computerized data are all interpreted based on similar studies performed by others and supported by related journals in proving the validation of the output. Over the things, the computerized data are the product amount and total time elapsed on each production which is automatically recorded by the system at the manufacturing site. Findings: The finding of this paper is firstly the exposure and emphasis of limitation exists in current implementation of OEE, which showing that high utilization of the machine is encouraged regardless of the customer demand and is having conflict with the inventory handling cost. This is certainly obvious with overproduction issue especially during low customer demand period. The second limitation in general implementation of OEE is the difficulty in obtaining the ideal cycle time, especially those equipments with constant process time. The section of this paper afterward comes out with the proposed solution in fixing this problem through the definition of performance ratio and then usage of this definition in measuring the machine utilization from time to time. Before this, the time available for the production is calculated incorporating the availability of OEE, which is then used to get the Takt time. Research limitations/implications: Future research should be conducted to test the possibility and to verify the definition of such performance ratio including Takt time on those processes of which its operating time is possibly to be reduced, especially those are not constant and fixed. This piece of research is temporarily done on the process where its operating time is constant from time to time and there is no ideal cycle time possible. Practical implications: The awareness of the overproduction should be emphasized and raised in the intention of pursuing higher OEE value. As the definition proposed such, the process with constant cycle time could even be defined in different performance ratio from time to time regarding to the customer demands and corresponding production rate. These two variables can be adjusted and balanced to increase the OEE value through optimization of average cycle time. Over this, optimization of average cycle time on equipment with constant operating time can be achieved through the optimization of loading number per each processing. Originality/value: The novelty of the paper is the inclusion of customer demand in obtaining OEE value of any particular equipment. Besides that, the equipment without ideal cycle time, which means those processes carried out in constant cycle time are possibly to be evaluated with performance ratio. As consequence of that, the machine utilization and capability used could be quantified and visualized using the performance ratio data of the OEE proposed.
Keywords: 650; Overall Equipment Effectiveness (OEE); Takt time; average cycle time; performance ratio; availability